ON A RATE OF CONVERGENCE IN THE GI|G|1|∞ MODEL - Grigoryan, T. A. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2003)
In the present paper one more estimation on a rate of convergence of actual waiting time to its stationary value in the GI|G|1|∞ model is obtained. It leads to a similar estimation for total empty time of a server when the traffic intensity of the model is more than one.